Christmas scarf murder - O'Connor, Carlene; Day, Maddie; Ehrhart, Peggy (Kensington Publishing Corp., 2022)
"They're coziest of wintertime accessories ... unless, of course, they become accessories to murder! USA Today bestselling author Carlene O'Connor teams up with Maddie Day and Peggy Ehrhart for a holly jolly Christmas collection of seasonal stories, as their beloved series sleuths each solve cases revolving around handknit Christmas scarves"--